Mandibular growth and dentoalveolar development in the treatment of Class II, division 1, malocclusion using Balters Bionator according to the skeletal maturation - Santos-pinto, Paulo Roberto Dos; Martins, Lidia Parsekian [UNESP]; Santos-pinto, Ary Dos [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Raveli, Dirceu Barnabé [UNESP]; Santos-pinto, Cristiane Celli Matheus Dos (Dental Press International, 2013)
OBJECTIVE: The purpose of the study was to evaluate the influence of the skeletal maturation in the mandibular and dentoalveolar growth and development during the Class II, division 1, malocclusion correction with Balters bionator. METHODS: Three groups of children with Class II, division 1, malocclusion were evaluated. Two of them were treated for one year with the bionator of Balters appliance in different skeletal ages (Group 1: 6 children, 7 to 8 years old and Group 2: 10 children, 9 to 10 years old) and the other one was followed without treatment (Control Group: 7 children, 8 to 9 years old). Lateral 45 degree cephalometric radiographs were used for the evaluation of the mandibular growth and dentoalveolar development. Tantalum metallic implants were used as fixed and stable references for radiograph superimposition and data acquisition. Student's t test was used in the statistical analysis of the displacement of the points in the condyle, ramus, mandibular base and dental points. Analysis of variance one-fixed criteria was used to evaluate group differences (95% of level of significance). RESULTS: The intragroup evaluation showed that all groups present significant skeletal growth for all points analyzed (1.2 to 3.7 mm), but in an intergroup comparison, the increment of the mandibular growth in the condyle, ramus and mandibular base were not statically different. For the dentoalveolar modifications, the less mature children showed greater labial inclination of the lower incisors (1.86 mm) and the most mature children showed greater first permanent molar extrusion (4.8 mm).

OBJETIVO: avaliar a influência da maturação óssea no processo de crescimento e de desenvolvimento mandibular e dentoalveolar durante a correção da Classe II, divisão 1, com o Bionator de Balters. MÉTODOS: foram avaliados três grupos de crianças com Classe II, divisão 1. Dois grupos foram tratados por um ano com o aparelho Bionator de Balters, em diferentes idades esqueléticas (Grupo 1: 6 crianças, com 7 a 8 anos de idade; e Grupo 2: 10 crianças, com 9 a 10 anos); e um grupo sem tratamento (Grupo controle: 7 crianças, com 8 a 9 anos). Telerradiografias laterais em norma de 45º foram utilizadas para a avaliação do crescimento mandibular e para o desenvolvimento dentoalveolar. Implantes metálicos de tântalo foram usados como referência fixa e estável para sobreposições radiográficas e aquisição de dados. Na análise estatística do deslocamento de pontos localizados na região de côndilo, corpo e base mandibular e de pontos dentários, foi empregado o teste t de Student; para avaliar as diferenças entre os grupos, usou-se a análise de variância a um critério de classificação (nível de significância de 95%). RESULTADOS: os grupos, quando avaliados individualmente, apresentaram crescimento de todos os pontos esqueléticos de forma significativa (1,2 a 3,7mm); porém, quando comparados entre si, a quantidade de crescimento na região do côndilo, ramo e base da mandíbula não foi estatisticamente diferente. Quanto às alterações dentárias, ocorreu maior inclinação dos incisivos inferiores para vestibular (1,86mm) nos pacientes menos maduros, e maior extrusão dos primeiros molares permanentes (4,8mm) nos pacientes mais maduros.
Crescimento mandibular e desenvolvimento dentoalveolar no tratamento da Classe II, divisão 1, com Bionator de Balters em função da maturidade esquelética
Keywords: Má oclusão de Angle Classe II; Ortopedia; Crescimento e desenvolvimento; Angle Class II malocclusion; Orthopedics; Growth and development